Total hip arthroplasty outcomes assessment using functional and radiographic scores to compare canine systems - Iwata, D.; Broun, H. C.; Black, A. P.; Preston, C. A.; Anderson, G. I. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
A retrospective multi-centre study was carried out in order to compare outcomes between cemented and uncemented total hip arthoplasties (THA). A quantitative orthopaedic outcome assessment scoring system was devised in order to relate functional outcome to a numerical score, to allow comparison between treatments and amongst centres. The system combined a radiographic score and a clinical score. Lower scores reflect better outcomes than higher scores. Consecutive cases of THA were included from two specialist practices between July 2002 and December 2005. The study included 46 THA patients (22 uncemented THA followed for 8.3 ± 4.7M and 24 cemented THA for 26.0 ± 15.7M) with a mean age of 4.4 ± 3.3 years at surgery. Multi-variable linear and logistical regression analyses were performed with adjustments for age at surgery, surgeon, follow-up time, uni- versus bilateral disease, gender and body weight. The differences between treatment groups in terms of functional scores or total scores were not significant (p > 0.05). Radiographic scores were different between treatment groups. However, these scores were usually assessed within two months of surgery and proved unreliable predictors of functional outcome (p > 0.05). The findings reflect relatively short-term follow-up, especially for the uncemented group, and do not include clinicianderived measures, such as goniometry and thigh circumference. Longer-term follow-up for the radiographic assessments is essential. A prospective study including the clinician-derived outcomes needs to be performed in order to validate the outcome instrument in its modified form.
Keywords: Hip; arthroplasty; canine; outcome assessment